Wrongful conduct of minors - FORTOVA, Lyubov (Journal of Education, Technology and Computer Science, 2014)
This article discusses the mechanisms and genealogy illegal behavior in children and adolescents. The role of the family as an institution of education juvenile delinquency prevention. Explores the role of social maturity of the person in the mechanism of formation of lawful behavior.